Squamate reptiles from Kanapoi: Faunal evidence for hominin paleoenvironments. Issue 140 (March 2020) - Head, Jason J.; Müller, Johannes
Abstract: The squamate fossil record from Kanapoi reveals generic to higher-order similarities with modern East African herpetofaunas. The record is derived from surface collection and screen washing, and consists primarily of isolated vertebrae with a few maxillary and mandibular elements. The most abundant remains are vertebrae of large-bodied Python that are morphologically similar to extant Python sebae, and vertebrae of Varanus cf. ( Varanus niloticus  +  Varanus exanthematicus ). Additional cranial and vertebral remains indicate the presence of lygosomine skinks, indeterminate Varanus, Viperidae, cf. Atractaspididae, and multiple colubrine morphotypes in the Kanapoi ecosystem. Despite similarities with modern herpetofaunas, the Kanapoi record lacks taxa common to other East African records, including agamids, chamaeleonids, amphisbaenians, the elapid Naja, and typhlopids. The overall composition of the Kanapoi squamate record is consistent with paleoenvironments similar to modern shrub savanna habitats. There are no indicators of canopied forest environments in squamate faunal composition. The fossil record of Kanapoi suggests that assembly of squamate faunas of modern East Africa was well underway by the late Neogene.